Pola Kepemimpinan Perempuan di Pondok Pesantren Darut Thayyibah dan Peran Sosialnya Di Masyarakat - Moh Zammil Al Muttaqin; Sigit Priyo Sembodo (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
This article aims to find out the leadership pattern of Ibu Nyai in the Darut Thayyibah Islamic boarding school and how the role of Ibu Nyai in the social environment of the community around the Islamic Boarding School is. The research used was qualitative with a descriptive qualitative research approach. The type of research used was ethnographic research using themethod life history in the data collection process. Data collection techniques through interview observations, and documentation, data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this study are: 1) Nyai Hj. Kholidah Thayyibah has an individual leadership pattern and a transformational leadership pattern using a contingency leadership style, 2) Apart from being a pesantren caregiver, Ibu Nyai is also active in various organizations, assemblies and as a female community leader who has a large enough mass base.